Digital Youth with Disabilities - Alper, Meryl (The John D. and Catherine T. MacArthur Foundation Reports on Digital Media and Learning, 2014)
An examination of media and technology use by school-aged youth with disabilities, with an emphasis on media use at home. Most research on media use by young people with disabilities focuses on the therapeutic and rehabilitative uses of technology; less attention has been paid to their day-to-day encounters with media and technology-the mundane, sometimes pleasurable and sometimes frustrating experiences of "hanging out, messing around, and geeking out." In this report, Meryl Alper attempts to repair this omission, examining how school-aged children with disabilities use media for social and recreational purposes, with a focus on media use at home. In doing so, she reframes common assumptions about the relationship between young people with disabilities and technology, and she points to areas for further study into the role of new media in the lives of these young people, their parents, and their caregivers. Alper considers the notion of "screen time" and its inapplicability in certain cases-when, for example, an iPad is a child's primary mode of communication. She looks at how young people with various disabilities use media to socialize with caregivers, siblings, and friends, looking more closely at the stereotype of the socially isolated young person with disabilities. And she examines issues encountered by parents in selecting, purchasing, and managing media for youth with such specific disabilities as ADHD and autism. She considers not only children's individual preferences and needs but also external factors, including the limits of existing platforms, content, and age standards.